Hubungan Karakteristik Inovasi dan Kearifan Lokal Terhadap Keberlanjutan Penerapan Teknologi Padi Salibu di Kabupaten Tanah Datar, Sumatera Barat - Sri Wahyuni; Zulvera Zulvera; Hery Bachrizal Tanjung; Ernita Arif (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2019)
Salibu technology is a local wisdom of rice technology in West Sumatera which has the spirit to help widows and poor families. The sustainability of rice implementation is determined by the characteristics of farmers, innovation characteristics, and farmers' perception of local wisdom. This study aims to: (1) describe the sustainability of salibu technology in Tanah Datar, and (2) to analyze the relationship between the characteristics of rice innovation and local wisdom with the sustainability of Salibu technology in Tanah Datar. This study was designed quantitatively using survey methods and supported by qualitative data. The location of the study was chosen purposively based on the location topography: Sungai Tarab representing lowland and Batipuh representing the plateau. The results showed that Sungai Tarab and Batipuh continue the rice technology salibu, by planting back rice at each planting season, using and expanding the area of land planted with salibu rice. The sustainability of salibu technology implementation in Sungai Tarab and Batipuh is more influenced by the characteristics of innovation and local wisdom than the characteristics of farmers. Innovation of salibu rice technology understood by farmers need to be conserved, besides salibu rice technology technology can be accepted by farmers because easy and cheap, so farmers can get bigger profit.